Validitas dan Reabilitas Metode Penilaian Students Oral Case Analysis (SOCA) pada Mahasiswa Tahap Sarjana Kedokteran - Sylvia Mustika Sari (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: Oral case presentations will be a vital component in medical career. The Student Oral Case Analysis (SOCA) is the assessment method of students’ ability in presenting their knowledge in case analysis, communication skills, and appropriate professional interactions. In fact, the studies in SOCA are still very limited. The aim of this study was to observe the validity and reliability of the oral assessment or SOCA in undergraduate medical education.Method: The cross sectional study in the third year students in the Medical Faculty of University Jenderal Ahmad Yani. Content-related validity was achieved by a panel expert in developing case and guide for examiners in SOCA, while concurrent validity was achieved by the correlation between SOCA and MCQ results. Inter-rater reliability was estimated by kappa coefficient.Results: The panel expert has done to receive the content validity. As concurrent validity evidence, the correlation between SOCA and MCQ result was 0.441 (p<0.01). Inter-rater reliability with the result of Kappa coefficient was 0.893 (p<0.01).Conclusion: The result shows that SOCA in undergraduate education was valid enough and reliable to assess the cognitive aspect.